2022
DOI: 10.1186/s12903-022-02045-0
|View full text |Cite
|
Sign up to set email alerts
|

What characterizes effective tooth brushing of daily users of powered versus manual toothbrushes?

Abstract: Background Recent data show comparable deficits in oral cleanliness after tooth brushing in habitual users of powered toothbrushes (PT) and manual toothbrushes (MT). The present analysis explores the origin of these deficits by relating aspects of the observed tooth brushing behaviour to plaque after tooth brushing. Methods Users of rotating-oscillating PT (N = 48) and of MT (N = 52) brushed their teeth the best they could while being filmed. Vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, the high prevalence of plaque-associated periodontal disease [57] suggests that individuals are not capable of effectively ensuring oral cleanliness by their oral hygiene behavior. In line with this, several studies consistently showed remaining plaque immediately after tooth brushing, particularly on the sections of the gingival margin and on inner teeth surfaces [818] Video-based observational studies indicate that the inadequate plaque removal might be a result suboptimal oral hygiene skills [13, 15, 1822]. In these studies, brushing performance is assessed by the analysis of brushing time and its distribution across teeth surfaces and sextants as well as of brushing movements.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the high prevalence of plaque-associated periodontal disease [57] suggests that individuals are not capable of effectively ensuring oral cleanliness by their oral hygiene behavior. In line with this, several studies consistently showed remaining plaque immediately after tooth brushing, particularly on the sections of the gingival margin and on inner teeth surfaces [818] Video-based observational studies indicate that the inadequate plaque removal might be a result suboptimal oral hygiene skills [13, 15, 1822]. In these studies, brushing performance is assessed by the analysis of brushing time and its distribution across teeth surfaces and sextants as well as of brushing movements.…”
Section: Introductionmentioning
confidence: 79%
“…The aim of the present study is therefore to examine whether the tooth brushing parameters analyzed in the above-mentioned observational studies occur in the same or similar extent when the brushing performance of individuals is not only observed once but repeatedly over time. In some of the mentioned observational studies participants were instructed to brush their teeth “to the best of their ability” [15, 17, 21, 22] and in others to “brush as usual” [18]. The present study examines the stability of the brushing behavior in terms of both best brushing and brushing as usual.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, these small clinically non=significant differences may, over time, differentially impact periodontal health. In contrast, a recent cross‐sectional study found no significant difference in plaque removal and gingivitis reduction between PTB and MTB users, who were not instructed in brushing techniques; according to the authors, both groups did not achieve satisfactory oral cleanliness (Petker et al, 2019), as they both neglected lingual surfaces and gingival margins (Petker‐Jung et al, 2022). Thus, in addition to recommending the use of PTBs, dentists should also give oral hygiene instructions.…”
Section: Discussionmentioning
confidence: 97%
“…Fourth, although the final regression model was adjusted for the risk factors of periodontitis, variables that we did not consider might have affected our results. In particular, tooth-brushing techniques and duration are important factors for biofilm removal [ 2 , 44 ]; however, these habit-related factors were not considered in this study. Hence, future studies should use a longitudinal design and adjust for multiple confounding variables that affect periodontal status to determine the association between handgrip strength and periodontitis.…”
Section: Discussionmentioning
confidence: 99%